Yoga therapy and the health of refugees - Gopalkrishnan, Narayan (Curtin University, 2012)
Refugees settling in Australia have many physical and mental health issues prior to arrival, issues that can be exacerbated by the settlement process. In Australia, the health needs of refugees are largely managed through a biomedical approach involving medication and/or psychotherapy and counseling. This approach stems from a clear separation between systems that deal with physical health issues and those dealing with mental health. The biomedical basis for working with refugee health issues has been useful up to an extent as the framework is very effective at disease control and prevention but is not so effective for chronic disease that is linked to multiple behavioral, socio-cultural as well as biological factors. Further, there are a number of other aspects of refugee health that biomedicine is unable to respond to effectively, such as cultural differences in understandings of health and illness, causality and healing, mind/body duality, as well issues of power relationships and structures. There is increasingly within Western medicine an awareness of the embodied interface between the spiritual, the social, the psychological and the biological being. Scholars argue that an integrated or holistic paradigm that incorporates the different aspects of health, including the biological, the psychological, the social and the cultural, would make for far better outcomes in terms of the health of refugees than the biomedical by itself.This thesis examines the role that yoga therapy, as a complementary therapy, can play in responding to the complex health issues of refugees settling in Australia. The research presented in this thesis utilized qualitative research methodology involving a literature review and document analysis, in-depth interviews and focus groups. The participants included people of refugee background who had taken part in yoga programs in Australia, as well as support workers, medical practitioners and complementary therapists. The thesis describes the perception of the health of refugees settled in Australia among service providers and refugees themselves, and the key factors impacting on this. It further looks at the existing mainstream responses in Australia to the health needs of refugees. It then critically analyses the role that complementary therapies like yoga therapy can play, and concludes that, particularly if they are incorporated within an integrative medicine framework, they have a significant contribution to make towards supporting the health needs of refugees. The thesis argues that holistic systems that address different levels of being and incorporate biomedical systems as well as complementary and alternative medicine systems (CAMs), such as yoga, massage and tai chi, will support the health needs of refugees in a culturally appropriate and effective way. The thesis finally presents recommendations of strategies for future policy and practice.